Effect of mercury in the influx and efflux of nutrients in the microalga Desmodesmus armatus (2023)
ABSTRACT: Anthropogenic activities such as mining and the metallurgical industry are the main sources of mercury contamination. Mercury is one of the most serious environmental problems in the world. This study aimed to investigate, using experimental kinetic data, the effect of different inorganic mercury (Hg2+) concentrations on the response of microalga Desmodesmus armatus stress. Cell growth, nutrients uptake and mercury ions from the extracellular medium, and oxygen production were determined. A Compartment Structured Model allowed elucidating the phenomena of transmembrane transport, including influx and efflux of nutrients, metal ions and bioadsorption of metal ions on the cell wall, which are difficult to determine experimentally. This model was able to explain two tolerance mechanisms against mercury, the first one was the adsorption of Hg2+ions onto the cell wall and the second was the efflux of mercury ions. The model predicted a competition between internalization and adsorption with a maximum tolerable concentration of 5.29 mg/L of HgCl2. The kinetic data and the model showed that mercury causes physiological changes in the cell, which allow the microalga to adapt to these new conditions to counteract the toxic effects. For this reason, D. armatus can be considered as a Hg-tolerant microalga. This tolerance capacity is associated with the activation of the efflux as a detoxification mechanism that facilitates the maintenance of the osmotic balance for all the modeled chemical species. Furthermore, the accumulation of mercury in the cell membrane suggests the presence of thiol groups associated with its internalization, leading to the conclusion that metabolically active tolerance mechanisms are dominant over passive ones.